2019
DOI: 10.3390/agriculture9040075
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heavy Rainfall Events on the Dry Matter Yield Trend of Whole Crop Maize (Zea mays L.)

Abstract: The objective of this study was to detect the historical dry matter yield (DMY) trend and to evaluate the effects of heavy rainfall events on the observed DMY trend of whole crop maize (WCM, Zea mays L.) using time-series analysis in Suwon, Republic of Korea. The climatic variables corresponding to the seeding to harvesting period, including the growing degree days, mean temperature, etc., of WCM along with the DMY data (n = 543) during 1982–2011, were used in the analysis. The DMY trend was detected using Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…percent of the annual PA [33], and the Korean rainfall concentrated in the summer monsoon season will likely become even more severe, increasing the chances of a long dry season in spring [23]. As to the severity of the spring drought, Lee (2015) reported that if there was no rain for more than two weeks, concerns about agricultural drought were particularly high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…percent of the annual PA [33], and the Korean rainfall concentrated in the summer monsoon season will likely become even more severe, increasing the chances of a long dry season in spring [23]. As to the severity of the spring drought, Lee (2015) reported that if there was no rain for more than two weeks, concerns about agricultural drought were particularly high.…”
Section: Discussionmentioning
confidence: 99%
“…identify the trends in yields and climatic factors as a form of climate change research in the Republic of Korea [21][22][23]. The drawback of performing this study using historical climate information was that it could not reflect abnormal climate conditions because only normal climates conditions because only normal climate conditions were taken into account.…”
Section: A C C E T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Remote sensing has been applied in many fields as it can estimate many of these factors [16,37,38,39,40,41,42,43]. Although ARIMAX has been used to study air pollution [44], corn yields [45], and to predict various illnesses [46], no one has used it to study brucellosis in recent years. In addition, the use of ARIMAX models helps to explore the relationship between time series and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were also carried out in economic plants, such as Chinese cabbage [21] and apple [22], in this region. For forage crops cultivated in this region, yield modeling studies based on climatic data were carried out on whole crop rye [23], Italian ryegrass [24], and whole crop maize [25]. However, no research expounding climatic, soil, and cultivar data-based yield modeling of forage crops cultivated in the southern area of the Korean Peninsula was reported.…”
Section: Introductionmentioning
confidence: 99%